Extending the Dispersive Optical Model to β-unstable Systems - Pruitt Cole D.; Perrotta Salvatore Simone; Escher Jutta; Gorton Oliver (EPJ Web of Conferences)
Phenomenological optical-model potentials (OMPs) are a key ingredient for nuclear cross section libraries that enter astrophysical nucleosynthesis simulations. While existing OMPs can reliably reproduce direct reaction cross sections on β-stable targets, the lack of scattering data on β-unstable targets limits the credibility of OMPs extrapolated to the extremely neutron-rich regime reached during explosive nucleosynthesis. Recent work with fully non-local dispersive OMPs indicates that even in regions where scattering data are unavailable, bound-state quantities, such as the proton and neutron number and binding energy, can serve as powerful constraints on the OMP. In this proceeding, we describe first steps toward a global, non-local, uncertainty-quantified, and fully dispersive OMP capable of leveraging both scattering and bound-state observables from stability to the driplines. As an example, we show how single-nucleon scattering data on traditional OMP training nuclei 40,48Ca, 90Zr, 112,124Sn, 208Pb can be combined with structural information to improve neutron capture cross sections at astrophysical energies relevant for the i-process and weak r-process.